Effects of Truncating the Height of Compound Parabolic Collector on its Geometry, Optical and Thermal Performances - ABDULLAHI, Bala; ABDURRAHMAN, Bala G.; ALHASAN, Yusuf; ABUBAKAR, Saidu B.; KUNYA, Bashir I.; Raya K. ALDADAH; MAHMOUD, Saad; REZK, Ahmed (FUDMA Journal of Engineering and Technology, 2026)
Radiation available, collector design and its orientation are the key parameters that affect the performance of any solar collector. At low concentrations, the concentrator of Compound Parabolic Collector (CPC) tends to be long and most of the top parts are not contributing to the radiation collection. Reducing the height (truncation) of those parts increases the optical efficiency at the expense of the concentration ratio. This work presents computational and experimental studies on the effects of truncation level of heat pipe-based compound parabolic collector (HPCPC) on its optical performance using solar radiation data from Kano, Nigeria (12.05oN). It aims to determine the effects of truncation at different truncation levels to determine the best level. Two computer programs were developed for the geometric characterization of symmetric low concentration compound parabolic collectors and for studying the effects of truncating its concentrator. Results showed that as the truncation levels increase, the collector height, aperture width, concentration ratio, and the average number of reflections decrease while the acceptance angle increases. The truncation effect was also studied using a validated advanced ray-tracing technique. Results showed that truncation increases the optical efficiency of the HPCPC but decreases its concentration ratio. From the graph of optic, low efficiency and concentration ratio against truncation level, results showed that the HPCPC with an acceptance angle of 60o and receiver radius of 12.5 (i.e. HPCPC60R12.5), HPCPC40R12.5 and HPCPC30R12.5 can be truncated respectively by 62%, 55% and 43% to achieve optical efficiencies/concentration ratios of 84%/1.65, 71%/2.55 and 55%/3.5.